Do Patient Education Materials on Female Pelvic Floor Disorders Meet Readability Standards? Putting Them to the Test. Issue 4 (5th July 2020) - Du, Chris; Lee, Wai; Lucioni, Alvaro; Kobashi, Kathleen; Lee, Una
Abstract: Introduction: Patient education materials are widely used vehicles to provide patients with health education. While the Joint Commission recommends patient education materials not exceed the 5th grade level and the National Institutes of Health the 7th grade level, studies show that patient education materials are routinely written above the 8th grade level. We assessed the readability of patient education materials available from national and international organizations on the topics of pelvic organ prolapse, overactive bladder and stress urinary incontinence. Methods: We identified available online, downloadable English language patient education materials on pelvic organ prolapse, overactive bladder and stress urinary incontinence from the American Urological Association, American Urogynecologic Society, Society of Urodynamics, Female Pelvic Medicine and Urogenital Reconstruction, International Continence Society, International Urogynecological Association, American College of Obstetricians and Gynecologists and National Association for Continence. We used 4 validated readability indices to evaluate patient education material texts and descriptive statistics to compare calculated readability grades. Results: We evaluated 7 patient education materials on pelvic organ prolapse, 8 on overactive bladder and 7 on stress urinary incontinence. Mean readability scores for pelvic organ prolapse, overactive bladder and stress urinary incontinence patient education materials were grade level 12.3 (range 9.1 to 16.7, SD 1.9), grade level 9.4 (range 5.1 to 17.9, SD 3.0) and grade level 11.5 (range 7.5 to 16.9, SD 2.5), respectively. Conclusions: Most patient education materials for pelvic organ prolapse, overactive bladder and stress urinary incontinence evaluated were written at a minimum of high school level and above the National Institutes of Health and Joint Commission recommended target readability. Developing and using patient education materials with the appropriate readability for the general patient population may enhance comprehension of the material and improve patient care for pelvic organ prolapse, overactive bladder and stress urinary incontinence.